The development of Vocational Secondary School students’ reflection and self-assessment skills in the context of critical constructivism - Kroiče, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
As the demands of labor market have increased, Vocational Secondary School students have to acquire the knowledge and skills level, which could help them to become highly qualified professionals who are able to compete in the labor market. The author explores the causes of poor results and options to prevent possible learning difficulties.A learning model, which is based on a critical constructivist didactic epistemology, has been proposed. This type of teaching encourages the learners to reflect on their learning aims, their personal meaning as well as existing experience; to evaluate, define and solve learning problems and if it is necessary to ask for support of the teacher; to evaluate learning results and to set new goals.The results of the research in Rezekne Technical School confirm that the development of reflection and self-assessment skills contributes to the quality of learning and helps to identify as well as to overcome learning difficulties.